Experimental studies of the parameters of flow movement along a dry riverbed under high-altitude conditions at a hydrodynamic accident - Striganova Марина Юрьевна; Shatalov Игорь Михайлович; Shcherbakova Мария Константиновна; Bandolik Николай Николаевич; Gudkov Алексей Александрович; Komzolova Дарья Сергеевна (Journal of Civil Protection, 2022)
Purpose. To experimentally investigate the nature of movement and parameters of non-stationary water flows in the lower reaches along a dry riverbed formed when the integrity is violated or the dam breaks under high-altitude conditions. Methods. Hydraulic calculations, experimental studies, video surveillance. Findings. A model of the hydraulic structure under consideration and a methodology for conducting the experiment have been developed. The nature of the moving flow during a hydrodynamic accident at a high-altitude dam is revealed. The height of the displacement wave in the design sections when the water flow moves along a sloping dry riverbed was determined experimentally. Application field of research. The obtained results can be used to predict the consequences of a possible hydrodynamic accident, which is necessary for the development of measures of population evacuation, elimination of the flooding consequences, and assessment of possible damage.